Permian–Triassic mass extinction pulses driven by major marine carbon cycle perturbations - Jurikova, Hana; Gutjahr, Marcus; Wallmann, Klaus; Flögel, Sascha; Liebetrau, Volker; Posenato, Renato; Angiolini, Lucia; Garbelli, Claudio; Brand, Uwe; Wiedenbeck, Michael; Eisenhauer, Anton (Nature Geoscience, 2020)
The Permian/Triassic boundary approximately 251.9 million years ago marked the most severe environmental crisis identified in the geological record, which dictated the onwards course for the evolution of life. Magmatism from Siberian Traps is thought to have played an important role, but the causational trigger and its feedbacks are yet to be fully understood. Here we present a new boron-isotope-derived seawater pH record from fossil brachiopod shells deposited on the Tethys shelf that demonstrates a substantial decline in seawater pH coeval with the onset of the mass extinction in the latest Permian. Combined with carbon isotope data, our results are integrated in a geochemical model that resolves the carbon cycle dynamics as well as the ocean redox conditions and nitrogen isotope turnover. We find that the initial ocean acidification was intimately linked to a large pulse of carbon degassing from the Siberian sill intrusions. We unravel the consequences of the greenhouse effect on the marine environment, and show how elevated sea surface temperatures, export production and nutrient input driven by increased rates of chemical weathering gave rise to widespread deoxygenation and sporadic sulfide poisoning of the oceans in the earliest Triassic. Our findings enable us to assemble a consistent biogeochemical reconstruction of the mechanisms that resulted in the largest Phanerozoic mass extinction.